Anatomy of the Antarctic Circumpolar Current volume transports through Drake Passage - Koenig, Zoé (2016)
The 20 year (October 1992 to August 2013) observation-based volume transport time series of the Antarctic Circumpolar Current (ACC) through Drake Passage (DP) across the Jason altimeter track #104 is analyzed to better understand the ACC transport variability and its potential causes. The time series of three transport components (total (TT), barotropic (BT), and baroclinic (BC)) referenced to 3000 m present energetic intraseasonal fluctuations, with a salient spectral peak at 50 and 36 days, with the largest (least) variance being associated with the BT (BC) component. Low-frequency variations are much less energetic with a significant variance limited to the annual and biannual timescales and show a nonstationary intermittent link with the Southern Annular Mode and the Nino 3.4 index for interannual timescales. The region around 57°S in the Yaghan Basin appears to be a strategic point for a practical monitoring of the ACC transport, as the whole-track TT is significantly correlated with the local TT (r = 0.53) and BT (r = 0.69) around 57°S. These local BT (and TT) variations are associated with a well-defined tripole pattern in altimetric sea level anomaly (SLA). There is evidence that the tripole pattern associated with BT is locally generated when the BC-associated mesoscale SLAs, which have propagated eastward from an upstream area of DP, cross the Shackleton Fracture Zone to penetrate into the Yaghan Basin. Barotropic basin modes excited within the Yaghan Basin are discussed as a plausible mechanism for the observed energy-containing intraseasonal spectral peaks found in the transport variability.